2011
DOI: 10.1017/s1047951111002058
|View full text |Cite
|
Sign up to set email alerts
|

Interventional treatment of critical coarctation of the aorta in an extremely low birth weight preterm neonate

Abstract: The authors describe successful balloon angioplasty of aortic coarctation in a preterm neonate weighing 670 grams. The intervention was performed in an open incubator to ensure stable temperature comfort and to minimise the risk of hypothermia during the procedure of obtaining surgical vessel access, performing balloon angioplasty, and closure of the wound.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
17
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 8 publications
0
17
0
Order By: Relevance
“…Although these studies demonstrated the feasibility of surgical correction, the reported rates of reintervention (34%) and mortality (18%) were very high [2][3][4][5] (Online Supplement Table 2). Percutaneous balloon dilatation can be considered as an alternative to surgery and has been described in 11 VLBW neonates at a median age of 14 days (2-34) and weight of 850 g (460 to 1500) [6][7][8][9][10][11] (Online Supplement Table 3). However, recoarctation does occur in up to 50% of infants treated with balloon dilatation before 6 months of age [14,15].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although these studies demonstrated the feasibility of surgical correction, the reported rates of reintervention (34%) and mortality (18%) were very high [2][3][4][5] (Online Supplement Table 2). Percutaneous balloon dilatation can be considered as an alternative to surgery and has been described in 11 VLBW neonates at a median age of 14 days (2-34) and weight of 850 g (460 to 1500) [6][7][8][9][10][11] (Online Supplement Table 3). However, recoarctation does occur in up to 50% of infants treated with balloon dilatation before 6 months of age [14,15].…”
Section: Discussionmentioning
confidence: 99%
“…In very low birth weight (VLBW) infants (≤1500 g) earlier treatment is sometimes warranted due to systemic hypoperfusion, pulmonary hyperperfusion and/or hypertension. Options for treatment include surgery [2][3][4][5], percutaneous balloon dilatation [6][7][8][9][10][11] and percutaneous stent implantation [12,13]. We reviewed our results of primary stent implantation as bridging therapy to surgery in VLBW infants with a critical CoA in whom PGE had to be discontinued.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, occasional cases of secondary hypertension and intracranial bleeding related to hypertension have also been reported. [1][2][3] Although performing balloon angioplasty for the recurrence of coarctation following surgical repair is a generally accepted procedure, using it for native coarctation in newborns is controversial due to the potential complications and high rate of restenosis. [1][2][3] Factors such as developments in newborn care and the availability of echocardiography may lead to the early recognition of severe coarctation before the appearance of clinical symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Surgical repair is the primary treatment for native coarctation of the aorta in newborns and infants. [1] Although experience in the use of balloon angiography for the treatment of this condition has gradually increased since it was first introduced in 1982, high rates of restenosis and complications such as an increased risk of aneurysm formation and damage to the peripheral artery involved in the procedure have been the main reasons that have prevented this procedure from becoming the treatment of choice. [2] However, balloon angioplasty has been performed as a palliative treatment in certain centers due to the high rates of mortality and morbidity associated with surgery in newborns presenting with the clinical manifestations of cardiogenic shock.…”
mentioning
confidence: 99%
“…Balloon angioplasty procedure in the treatment of native coarctation of the newborn is controversial due to high rates of restenosis[1] and complications such as increased risk of aneurysm formation and damage to the peripheral artery involved in the intervention. [23] We believe that in such small and sick subset of babies, balloon angioplasty is a very good palliative procedure because doing surgery in these babies is having high rates of complications.…”
mentioning
confidence: 99%